Treatments to refine one’s bodily beauty according to the teachings of Trota of Salerno - Glusiuk, Anna (Saeculum Christianum. Pismo Historyczne, 2021)
Trotula of Salerno lived in eleventh century Italy and was one of the few women who received an excellent education. Trotula was an unusual woman who, thanks to her talents, became famous not only in Salerno, but also in the whole of Italy and outside of the country. Her name can be found in various medieval writings, as for example in the Canterbury Tales written by Geoffrey Chaucer. She was not only a doctor, but also the author of medical treatises. One of her works, entitled De ornatu mulierum, shows what kind of “cosmetics” the women of medieval Salerno used. Thanks of her writings, it is known how the women of the time took care of their bodies. She taught how to remove unwilling hair, and that it was necessary to have white, healthy teeth, smooth skin, and long black or blonde hair.